(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The stand-alone computer course is the earliest IT training model in teacher education. Designed in the early 2000s, the course responded to increasing demands from schools that teachers have adequate technology skills. The primary goal was to improve technology proficiency among pre-service teachers. Research later determined that student teachers and recent graduates continued to have difficulty relating technology to instructional activities and lacked strategies to integrate computers in the curriculum.This result prompted severe criticism of the stand-alone computer course. Computers, it was argued, should not be taught in isolated technology courses but integrated into all education courses, especially methods courses, so that faculty could model the integration of computers in teaching content areas.